2023
DOI: 10.1111/dme.15259
|View full text |Cite
|
Sign up to set email alerts
|

Standardising personalised diabetes care across European health settings: A person‐centred outcome set agreed in a multinational Delphi study

Ann‐Kristin Porth,
Anouk Sjoukje Huberts,
Alizé Rogge
et al.

Abstract: ObjectiveStandardised person‐reported outcomes (PRO) data can contextualise clinical outcomes enabling precision diabetes monitoring and care. Comprehensive outcome sets can guide this process, but their implementation in routine diabetes care has remained challenging and unsuccessful at international level. We aimed to address this by developing a person‐centred outcome set for Type 1 and Type 2 diabetes, using a methodology with prospects for increased implementability and sustainability in international hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Gender differences, social determinants of health and the promotion of interdisciplinary care are also important. If we include all these factors in the shared decision-making process, clinical outcomes are likely to be better and adherence and persistence may be improved [ 71 ].…”
Section: Therapeutic Translation: Dysfunctional Adipose Tissue Approa...mentioning
confidence: 99%
“…Gender differences, social determinants of health and the promotion of interdisciplinary care are also important. If we include all these factors in the shared decision-making process, clinical outcomes are likely to be better and adherence and persistence may be improved [ 71 ].…”
Section: Therapeutic Translation: Dysfunctional Adipose Tissue Approa...mentioning
confidence: 99%
“…2 The review called on healthcare professionals (HCPs) to discuss sexual problems within clinical consultations and for awareness that FSD may be linked to advanced diabetes complications. A Delphi review highlighted the importance of sexual health (including sexual dysfunction) to people with diabetes 3 and a systematic review concluded FSD is a significant issue for women with type 1 diabetes. 4 According to Diagnostic and Statistics Manual V, 5 FSD describes a disorder of sexual interest/−arousal and/or genitopelvic pain/penetration, and/or orgasm.…”
Section: Introductionmentioning
confidence: 99%